IMPACT OF ARTIFICIAL INTELLIGENCE AND DIGITAL ECONOMY ON INDUSTRIAL REVOLUTION 4: EVIDENCE FROM BANGLADESH - Iqbal, Mohammed Masum; Islam, K. M. Anwarul; Zayed, Nurul Mohammad; Beg, Tahrima Haque; Shahi, Shahiduzzaman Khan (American Finance & Banking Review, 2021)
This research investigates effects of artificial intelligence and digital economy on the 4th industry revolution from the perspective of Bangladesh. Artificial intelligence affecting the labor market both positively and negatively. Because of artificial intelligence, few existing jobs have been demolished and few new jobs have been emerged as well. Digital economy in Bangladesh is now an emerging issues with the blessings of artificial intelligence. Few employment opportunities will be created in Bangladesh because of emerging digital economy. The objective of this research is to analyze these opportunities and come out with few policy recommendations to implement towards industry revolution 4. Secondary data have been used along with recent relevant literatures to achieve the above stated objective as this is an empirical research. Ideas regarding revised national plan, financial tools, emerging digital economy in Bangladesh are the prominent outcome of this research. The policy recommendations of managing the gap between digital economy and industry revolution 4 regarding artificial intelligence could be helpful to The Government of the Peoples’ Republic of Bangladesh to implement policies.   JEL Classification Codes: L0, D74.